PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP DISIPLIN KERJA MELALUI KEADILAN ORGANISASI PADA SEKRETARIAT DAERAH KABUPATEN SERANG - Nurhayati, Ati; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2018)
Human resources is a matter of great concern in every organization, this study aims to determine the influence of organizational culture, leadership to Discipline work with Organizational Justice as intervening variables, research conducted on the Secretariat of the District Kab.Serang, with a sample of 125 Employees, in the analysis using the SEM method, the results show that organizational culture has no positive effect on the discipline of work , Leadership positively affects work discipline and organizational justice as intervening variable .